DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON WORDWALL GAMES TO INCREASE MOTIVATION AND ELEMENTARY SCHOOL STUDENTS' LEARNING INTERESTS - Evandri (LPPM UNiversitas Bina Mandiri Gorontalo, 2024)
WordWoll game-based interactive learning media combines elements of education and entertainment, creating a fun and effective learning environment. In this article, we will discuss in depth how the development of this learning media can be an innovative solution in increasing students' interest in learning and understanding. Interactive media based on the Wordwoll (Word of the World) game is the latest innovation in the development of technology-based education. This approach combines game elements with an understanding of the world to create a deeper and more enjoyable learning experience. In this article, we will discuss the development of wordwoll game-based interactive media using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model to ensure effectiveness and efficiency in the learning process. By using qualitative research methods. As a result, the use of technology in education can create a positive impact and bring learning to a more innovative level. Thus, the development of interactive media based on the WordWoll game using the ADDIE model is a step forward in producing a generation of learners who are ready to face the future.